2006
DOI: 10.1387/ijdb.062168as
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylgalactosamine 4-sulfate 6-O-sulfotransferase expression during early mouse embryonic development

Abstract: N-acetylgalactosamine 4-sulfate 6-O-sulfotransferase (GalNAc4S-6ST) is an enzyme which is known to help build up the GlcAβ1-3GalNAc(4,6-bisSO 4 ) unit of chondroitin sulfate E (CS-E). This enzymatic activity has been reported in squid cartilage and in human serum, but has never been reported as an enzyme required during early mouse development. On the other hand, CS-E has been shown to bind with strong affinity to Midkine (MK). The latter is a heparin-binding growth factor which has been found to play importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In fact, their conclusion is that proteoglycans (especially CSPG) are involved in neural fold elevation and convergence as well as in the migration processes of neural crest cells, and no reference is made to the fusion process. Our results are supported by a recent study [Salgueiro et al, 2006] which demonstrated the selective expression, on the tip of mouse neural folds immediately prior to their fusion, of specific enzymes involved in CSPG synthesis. In addition, the selective digestion of CSPG with a specific glycosidase (chondroitinase AC) causes fusion defects in the otic vesicle [Gerchman et al, 1995], the crystalline vesicle [Gato et al, 2001] and the palate [Gato et al, 2002].…”
Section: Discussionsupporting
confidence: 89%
“…In fact, their conclusion is that proteoglycans (especially CSPG) are involved in neural fold elevation and convergence as well as in the migration processes of neural crest cells, and no reference is made to the fusion process. Our results are supported by a recent study [Salgueiro et al, 2006] which demonstrated the selective expression, on the tip of mouse neural folds immediately prior to their fusion, of specific enzymes involved in CSPG synthesis. In addition, the selective digestion of CSPG with a specific glycosidase (chondroitinase AC) causes fusion defects in the otic vesicle [Gerchman et al, 1995], the crystalline vesicle [Gato et al, 2001] and the palate [Gato et al, 2002].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, caution should be taken in inferring a link between filopodial activity and AVE cell movement before more direct evidence is available. An alternative possibility is that DVE cells might migrate in response to cues from the underlying basement membrane (Rodriguez et al 2005; Salgueiro et al 2006). Various planar cell polarity (PCP) proteins are expressed in the DVE/AVE (Crompton et al 2007), suggesting that DVE/AVE cells might move through planar polarity-dependent cellular rearrangement within the visceral endoderm epithelium.…”
Section: The Anterior Visceral Endoderm: Movement Form and Functionmentioning
confidence: 99%
“…We have performed a differential screening using a generated transgenic mouse line in which EGFP is expressed in the AVE, under the control of the promoter region of the Cerl-1 gene. Gene expression profiling using GeneChips ® (Affymetrix ®) identified novel differentially expressed transcripts at the very early stages of A-P axis establishment (Mário Filipe, unpublished), some of them now currently being studied at our laboratory Filipe et al, 2006;Salgueiro et al, 2006). We expect that this approach will allow us to learn more about asymmetry generation, tissue patterning and specification during early vertebrate development and that this knowledge can be applied in the future to regenerative medicine.…”
Section: Final Remarksmentioning
confidence: 99%